2011
DOI: 10.1002/emmm.201100158
|View full text |Cite
|
Sign up to set email alerts
|

The isoenzyme of glutaminyl cyclase is an important regulator of monocyte infiltration under inflammatory conditions

Abstract: Acute and chronic inflammatory disorders are characterized by detrimental cytokine and chemokine expression. Frequently, the chemotactic activity of cytokines depends on a modified N-terminus of the polypeptide. Among those, the N-terminus of monocyte chemoattractant protein 1 (CCL2 and MCP-1) is modified to a pyroglutamate (pE-) residue protecting against degradation in vivo. Here, we show that the N-terminal pE-formation depends on glutaminyl cyclase activity. The pE-residue increases stability against N-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
132
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(137 citation statements)
references
References 53 publications
3
132
2
Order By: Relevance
“…N-terminal pyroglutamate residues have been described for a number of hormones and secreted proteins (31). For example, the N terminus of monocyte chemoattractant protein 1 (CCL2/MCP-1) is modified to a pyroglutamate residue, thereby protecting it against degradation (32). MCP-1 plays a pivotal role in different inflammatory conditions (33).…”
Section: Discussionmentioning
confidence: 99%
“…N-terminal pyroglutamate residues have been described for a number of hormones and secreted proteins (31). For example, the N terminus of monocyte chemoattractant protein 1 (CCL2/MCP-1) is modified to a pyroglutamate residue, thereby protecting it against degradation (32). MCP-1 plays a pivotal role in different inflammatory conditions (33).…”
Section: Discussionmentioning
confidence: 99%
“…32,33 The elevated expression levels of all these molecules explain the exaggerated inflammation response that characterizes septic shock. Moreover, the CD276 molecule precursor (B7-H3), which was up-modulated under LD conditions at 6 dpf, functions as both a costimulator of proinflammatory cytokine release through NFKB 34 and a co-inhibitor to control the exuberant immune responses.…”
Section: Sepsis and Tolerance To Lps In Zebrafishmentioning
confidence: 99%
“…Interestingly, the oncogenic fusion protein RET/PTC expressed in PTC activates the transcription factor NF-kB and induces CCL2 gene expression (Russell et al 2003, Neely et al 2011. Recently, others and we have shown that the chemotactic activity of CCL2 depends on a modified N-terminus of the polypeptide, particularly the formation of a pyroglutamate (pE)-residue protecting against proteolytic degradation in vivo (Cynis et al 2011, Chen et al 2012. The formation of the N-terminal pE-residue is an important maturation step during synthesis and secretion of not only CCL2 but also hormones such as thyreotropin-releasing hormone and GNRH (Goren et al 1977, Abraham & Podell 1981, Awade et al 1994.…”
Section: Introductionmentioning
confidence: 99%